2008
DOI: 10.5172/conu.673.31.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Perception of intensive care unit stressors by patients in Malaysian Federal Territory hospitals

Abstract: The Intensive Care Unit (ICU) is a therapeutic place for monitoring critically ill patients. However, it is a stressful area for the patients and it is causing them great anxiety. Previous studies have identified three groups of stressors in ICU namely; physical, psychological and environmental. The aims of this study were to determine the ICU stressors as experienced by patients and to determine the level of stressors felt by patients in ICU. A cross sectional study was done on 70 patients from two tertiary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
2
11
0
3
Order By: Relevance
“…This result is similar to those found in the studies carried out by Soh, Soh, Ahmad, Abdul Raman, and Japar (2008), Fernandes da Cruz, Machado, Fernandes da Cruz, and Salazar Posso (2013) which found no high levels of stress. This result confirms that there are no universally stressful events, they only exist when a person defines them as such.…”
Section: Discussionsupporting
confidence: 92%
“…This result is similar to those found in the studies carried out by Soh, Soh, Ahmad, Abdul Raman, and Japar (2008), Fernandes da Cruz, Machado, Fernandes da Cruz, and Salazar Posso (2013) which found no high levels of stress. This result confirms that there are no universally stressful events, they only exist when a person defines them as such.…”
Section: Discussionsupporting
confidence: 92%
“…Good pain control decreases these complications (12). In Malaysia, Soh et al (13) found that pain was the most frequent complaint of patients. In our study, although 51% of the patients were postoperative, pain was ranked 5th among stress factors.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Pain increases secretion of cortisol and production of proinflammatory cytokines, and these increases may be deleterious to muscle. 24 Administration of morphine for pain management decreases the serum level of inflammatory cytokines, suggesting that managing pain may be muscle protective.…”
Section: Setting and Samplementioning
confidence: 99%